2020
DOI: 10.1093/mnras/staa1817
|View full text |Cite
|
Sign up to set email alerts
|

The compact triply eclipsing triple star TIC 209409435 discovered with TESS

Abstract: We report the discovery in TESS Sectors 3 and 4 of a compact triply eclipsing triple star system. TIC 209409435 is a previously unknown eclipsing binary with a period of 5.717 d, and the presence of a third star in an outer eccentric orbit of 121.872-d period was found from two sets of third-body eclipses and from eclipse timing variations. The latter exhibits signatures of strong third-body perturbations. After the discovery, we obtained follow-up ground-based photometric observations of several binary eclips… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…For example, Borkovits et al (2016) has reported 22 triple star candidates with outer period P 2 ≤ 240 d among the eclipsing binaries in the original Kepler-field, and only for five of them was an outer eccentricity of e 2 ≤ 0.1 found. More specifically, considering only the flat, compact hierarchical triple systems with accurately known parameters tabulated in Table 5 of Borkovits et al (2020b) only one of them has outer orbit less eccentric than e 2 ∼ 0.2. This only ex-ception, HD 181068 is similar to the present system not only in its flatness, but it also has two circular orbits (Borkovits et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Borkovits et al (2016) has reported 22 triple star candidates with outer period P 2 ≤ 240 d among the eclipsing binaries in the original Kepler-field, and only for five of them was an outer eccentricity of e 2 ≤ 0.1 found. More specifically, considering only the flat, compact hierarchical triple systems with accurately known parameters tabulated in Table 5 of Borkovits et al (2020b) only one of them has outer orbit less eccentric than e 2 ∼ 0.2. This only ex-ception, HD 181068 is similar to the present system not only in its flatness, but it also has two circular orbits (Borkovits et al 2013).…”
Section: Resultsmentioning
confidence: 99%
“…p 05 phase sections of the regular eclipses were kept, with the exception of the outer eclipses, where longer, 6-8-day-long sections of the light curves were also retained. Note that, in case of the WASP light curve, our treatment slightly departed from that which was followed in Borkovits et al (2020b), where the full WASP light curve was considered in the photodynamical analysis. The reason is that, in the present situation, the TESS light curve by itself made it possible to determine accurately the outer period and, therefore, we were able to pre-compute the expected locations of the outer eclipses in the intervals of the WASP observations.…”
Section: Joint Analysis Of the Available Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Hajdu et al (2017) identified five relatively short period Algol systems observed in the 100-150 d long CoRoT ETV data series for which the computed periods of the outer bodies are between 82 and 272 d. Although their solution does not satisfy the criterion that observations should cover at least two outer orbital periods (Conroy et al 2014;Borkovits et al 2016) their solutions were found to be physically consistent. Later short triple candidates were revealed from K2 data (Borkovits et al 2019a, b) and most recently from TESS data (Borkovits et al 2020). Test on a synthetic EB: raw (top panel) and phased (middle panel) synthetic LCs of a detached EB with period variations, generated using PHOEBE 2.0, are shown, along with the ETV diagram constructed with ToM calculated by our pipeline (bottom).…”
Section: Times Of Minimum Light Computationmentioning
confidence: 99%